JUEZ CONSTITUCIONAL: LEGISLADOR POSITIVO CONSTITUTIONAL (2016)
In Colombia, from the 1991 Constitution, the Constitutional Court has played an important role in the development of law, stating further conversion of Colombia in a “ neoconstitucionalista”, thus confirming that the right is of the judges and not legislators, the performances of the high courts called “ closure members “ on some occasions have become positive legislators, and beyond computers of public policies, functions and constitutional theory pertaining to other branches of the executive public power and legislative different to which they belong as is the judiciary.That condition where the legislative power is the one who can legitimately issue laws, has changed, now the judicial precedent issued by any of the high courts also have force of law erga omnes, requiring citizens without this provision be included in a standard, and that constitutionally has the legitimacy and acceptance by the citizens even more the case in the protection of rights regarding the conditions of human dignity is concerned.This time the study of the role of judge as positive legislator in recognizing social and cultural rights as fundamental rights and legitimacy of the judge to invade the sphere of legislative power is made.In addition, in the case of the constitutional court, he has not only played as a positive legislator, even a positive constituent, giving the category of fundamental rights positively are not, or interpreting the law in the constitutional sense in favor of recognition of fundamental rights and invading the purview of the legislature, even to create some legal uncertainty. The court also has played the role corresponding to executive, setting public policy as it is the case of decisions which declares unconstitutional state of affairs and ordering the executive take direction public policies aiming at the protection of fundamental rights.